Visible vs Silent Protest: Explaining Divergent Outcomes on Single-Candidate Local Elections in Indonesia - Hafidz, Moh. Maskurudin; Nailufar, Faza Dhora; Sembiring, Odri Prince Agustinus D; Rohi, Rudi (Jurnal Transformative: Ilmu Pemerintahan, 2025)
This study investigates the puzzling phenomenon of divergent outcomes in single-candidate local elections (Pilkada) across Indonesia. Employing a mixed-methods sequential explanatory design, this study undertakes a comparative analysis of three cases from the 2024 Pilkada in Bangka, Bangka Selatan, and Pangkalpinang, which are located within Bangka Belitung Islands Province. The approach utilizes quantitative survey data from 455 voters and qualitative document analysis. The results suggest that the key determinant of the blank vote's success or failure is the voter's evaluation of the incumbent's performance. Inadequate evaluations of the incumbent's performance in Bangka and Pangkalpinang served as a catalyst, converting a pre-existing crisis of representation into a successful protest vote. Conversely, high public satisfaction with governance in Bangka Selatan served as a protective barrier, neutralizing the impulse for protest despite the non-competitive electoral format. The analysis delineates two separate mobilization tactics for achieving victory: a "Visible Protest" in Pangkalpinang, led by a structured and identifiable social movement, and a "Silent Protest" in Bangka, emerging from the uncoordinated accumulation of individual discontent. This study enhances the comprehension of protest voting by identifying incumbent performance as a significant moderating influence. It underscores the voter's aptitude for constrained rationality and pragmatic decision-making, illustrating their resilience in utilizing institutional tools to hold political leaders accountable in a hard democratic context.